Análise tribológica do contato entre insertos de WC/Co e amostras de concreto de diferentes resistências à compressão uniaxial - Vallim, André de Lima (2022)
The need to understand the tribological system associated with the contact between carbide mining drill inserts and rocky substrates comes from the industry’s growing concern with wear processes and their associated losses and from its interest in optimizing the mining process through increase in penetration rates. The present study aims to simulate the tribological system formed by mining inserts and rocky substrates through tests on concrete samples, seeking to evaluate the variation of wear and penetration rates associated with the system through the variation of the uniaxial compressive strength of the concrete and the tangential cutting speeds in order to simulate different rock categories under different cutting regimes and to evaluate the influence of the variation of these factors on the analyzed parameters. Tribometer tests were carried out and parameters such as friction force, penetration rate, roughness parameters, affected contact area and surface composition were evaluated for each test configuration, these values were then compared to assess the significance of the compressive strength variation and the tangential speed of operation, analysis of variance were performed on each of the parameters analyzed. Variations were observed for most parameters when comparing test configurations, however the analysis of variance did not identify significant variations that could justify the influence of the varied factors on the results obtained, the wear and surface composition analysis identified hard metal wear mechanisms already known, such as cobalt matrix removal and the appearance of intragranular cracks, decreasing variations in the contact area with increasing uniaxial compressive strengths were also identified. The test configurations used did not show significant variations between their parameters. It can be concluded that, for the configurations used and despite being relevant factors to identify variations in the affected insert contact areas and in the surface composition of these inserts, compressive strength and insert operating speed are not relevant factors to evaluate friction coefficients and penetration rates, making it necessary to use other methods to compare these parameters between concrete samples that aim to simulate different rock formations.